2010
DOI: 10.4238/vol9-2gmr773
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different models to estimate genetic parameters for carcass traits in a commercial broiler line

Abstract: ABSTRACT. The effect of genetic and non-genetic factors for carcass, breast meat and leg weights, and yields of a commercial broiler line were investigated using the restricted maximum likelihood method, considering four different animal models, including or excluding maternal genetic effect with covariance between direct and maternal genetic effects, and maternal permanent environmental effect. The likelihood ratio test was used to determine the most adequate model for each trait. For carcass, breast, and leg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…This is likely due to the fact that in the present study the age of the birds at the time of measuring the traits was 17 to 18 wk, compared to an age of 5 to 6 wk in chickens. However, while this percentage may seem low, studies comparing models including and excluding maternal effects have shown that omission of the maternal effects may result in an overestimation of the direct heritability (e.g., Koerhuis and Thompson, 1997; Clément et al, 2001; Grosso et al, 2010). To evaluate the effect of the permanent environmental effect of the dam, all 4 models also were run without this effect, which resulted in increased heritabilities for the leg health traits in the range of 0.01 to 0.06.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to the fact that in the present study the age of the birds at the time of measuring the traits was 17 to 18 wk, compared to an age of 5 to 6 wk in chickens. However, while this percentage may seem low, studies comparing models including and excluding maternal effects have shown that omission of the maternal effects may result in an overestimation of the direct heritability (e.g., Koerhuis and Thompson, 1997; Clément et al, 2001; Grosso et al, 2010). To evaluate the effect of the permanent environmental effect of the dam, all 4 models also were run without this effect, which resulted in increased heritabilities for the leg health traits in the range of 0.01 to 0.06.…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that if a negative dependence exists between direct and maternal genetic effects, the dam either gives her offspring a plus set of genes for the direct additive effect and a poor maternal effect, or vice versa (Szwaczkowski, 2003). Moreover, some authors have suggested that negative estimates of medium to high magnitude for r am can be related to the size of the data set, its structure, and the magnitude of the direct and maternal additive genetic variances (Grosso et al, 2010;Heydarpour et al, 2008).…”
Section: Reproduction Traitsmentioning
confidence: 93%
“…Studies comparing models with and without maternal effects show that the direct heritability may be overestimated if significant maternal environmental effects are not fitted (e.g., Koerhuis and Thompson, 1997;Clément et al, 2001;Grosso et al, 2010). To evaluate the effect of not fitting this effect, line B was analyzed using a model without PEm.…”
Section: Heritabilitiesmentioning
confidence: 99%